Sistem Informasi Pembayaran Uang Sampah Rumah Tangga - Donna Saputri Br Ginting; Rahmayani Syahfitri (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Every day household waste cleaning activities are carried out by janitors, where every month a manual payment system is carried out. This is not very effective, and it takes a lot of time because officers have to go to people's homes to process payments. Through this practical work, it is hoped that they will be able to design an information system about paying household waste money in the village. The program used to manage the payment of household waste money in the village is Visual Basic 2008. And the results obtained from this information system will be used in the future, to assist in the development of a better system.